Accounting and Preserving the American Way of Life - Walker, Stephen P. (Contemporary Accounting Research, 2015)
Abstract Responding to calls to instate the visual in accounting history research, this study utilizes photographic images to reveal the role of accounting in the attempt to preserve an ideal (ruralism) and an institution (the family farm) in the United States . These elemental features of the American way of life were threatened during the interwar depression, resulting in governmental programs to secure their restoration. The analysis of official imagery reveals how the accounting prescriptions attending state intervention in agriculture were deemed conducive to the fortification of the economic, social and political foundations of agrarian living. Documentary photographs propagated the notion that accounting facilitated companionate marriage and the inclusive family. They also suggested that accounting was a focus for encouraging the communitarian endeavor, democratic participation and receptivity to state interventionism considered necessary to preserve the rural mode of living.